2020
DOI: 10.3390/su12135286
|View full text |Cite
|
Sign up to set email alerts
|

ICT Integration into Science Education and Its Relationship to the Digital Gender Gap

Abstract: The objective of the research is to know whether the use of technologies in the teaching of sciences, in the face of more traditional methods, influences gender differences, justifying the low enrolment of women in technical careers. The study was developed using a pretest–posttest quasi-experimental method through a nonequivalent control group with traditional methodology and common instruments such as the textbook, while in the experimental group, methodologies based on the management of ICT tools were made.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…Nevertheless, most studies have found significant differences in digital competence between men and women, for example, women seem to be less competent [35], but some researchers do not find differences [20,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, most studies have found significant differences in digital competence between men and women, for example, women seem to be less competent [35], but some researchers do not find differences [20,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…This also includes female teachers [37]. Nevertheless, not all studies have found these differences in digital competence when analysing the variable of gender [18,20,44], even with teachers in training [45,46]. In this sense, [47] found that men and women do not differ much in their online skills.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reasons for this gap is the intention to use technology [85], as women are more strongly influenced by perceived ease of use than men. Some studies have indicated the existence of a certain gender bias in the use of ICT tools, these tools being considered as more masculine in nature [86], both in work environments [87] and in training environments [88]. Therefore, the gender differences found in the study regarding the eco-sustainable use of ICT could be a consequence of the digital gender gap and not of women's lower environmental awareness [89].…”
Section: Positive Self-perception Of Males In the Eco-responsible Usementioning
confidence: 99%